2019
DOI: 10.1007/s42452-019-0958-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a non-nuclear density gauge as an alternate to destructive coring for airport asphalt acceptance testing

Abstract: A non-nuclear density gauge (NNDG) was evaluated as part of an asphalt runway resurfacing project. The repeatability of the NNDG was found to be high but asphalt temperature and surface moisture had a significant effect on the reliability of NNDG inferred asphalt density. It was also found that a single NNDG inferred density, located immediately over the core location, provided greater agreement with core density than an averaged NNDG density over and around the location of the core. It was concluded that when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…White evaluated a nonnuclear density gauge (NNDG) as part of an asphalt runway resurfacing project. It was concluded that when the temperature had stabilized and the surface was dry, the nonnuclear density gauge (NNDG) was a reliable replacement for destructive coring for density measurement [5]. Hu examined the possibility of utilizing Compaction Meter Value (CMV) to evaluate the density of different asphalt pavement layers [6].…”
Section: Introductionmentioning
confidence: 99%
“…White evaluated a nonnuclear density gauge (NNDG) as part of an asphalt runway resurfacing project. It was concluded that when the temperature had stabilized and the surface was dry, the nonnuclear density gauge (NNDG) was a reliable replacement for destructive coring for density measurement [5]. Hu examined the possibility of utilizing Compaction Meter Value (CMV) to evaluate the density of different asphalt pavement layers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Whereby, a high-quality asphalt binder can prevent or delay the environmental-and-traffic-related distresses in flexible pavements and hence increase the longevity of these pavements. Asphalt pavement distresses, i.e., rutting and cracking, occur before the time that flexible pavements reach their service lives [8,9]. These distresses result in huge amounts of money spent on rehabilitation or even reconstruction of flexible pavements; hence, it would be wiser to prevent such expenditures when it is possible to develop more sustainable and more resilient asphalt binders [10,11].…”
Section: Introductionmentioning
confidence: 99%